Morphology, ultrastructure, and molecular phylogeny of Wangodinium sinense gen. et sp. nov. (Gymnodiniales, Dinophyceae) and revisiting of Gymnodinium dorsalisulcum and Gymnodinium impudicum - Luo, Zhaohe; Hu, Zhangxi; Tang, Yingzhong; Mertens, Kenneth Neil; Leaw, Chui Pin; Lim, Po Teen; Teng, Sing Tung; Wang, Lei; Gu, Haifeng (Wiley, 2018)
The genus Gymnodinium includes many morphologically similar species, but molecular phylogenies show that it is polyphyletic. Eight strains of Gymnodinium impudicum, Gymnodinium dorsalisulcum and a novel Gymnodinium-like species from Chinese and Malaysian waters and the Mediterranean Sea were established. All of these strains were examined with light microscopy, scanning electron microscopy and transmission electron microscopy. SSU, LSU and internal transcribed spacers rDNA sequences were obtained. A new genus, Wangodinium, was erected to incorporate strains with a loop-shaped apical structure complex (ASC) comprising two rows of amphiesmal vesicles, here referred to as a new type of ASC. The chloroplasts of Wangodinium sinense are enveloped by two membranes. Pigment analysis shows that peridinin is the main accessory pigment in W. sinense. Wangodinium differs from other genera mainly in its unique ASC, and additionally differs from Gymnodinium in the absence of nuclear chambers, and from Lepidodinium in the absence of Chl b and nuclear chambers. New morphological information was provided for G. dorsalisulcum and G. impudicum, e.g., a short sulcal intrusion in G. dorsalisulcum; nuclear chambers in G. impudicum and G. dorsalisulcum; and a chloroplast enveloped by two membranes in G. impudicum. Molecular phylogeny was inferred using maximum likelihood and Bayesian inference with independent SSU and LSU rDNA sequences. Our results support the classification of Wangodinium within the Gymnodiniales sensu stricto clade and it is close to Lepidodinium. Our results also support the close relationship among G. dorsalisulcum, G. impudicum, and Barrufeta. Further research is needed to assign these Gymnodinium species to Barrufeta or to erect new genera.